2011
DOI: 10.1128/jcm.00319-11
|View full text |Cite
|
Sign up to set email alerts
|

First Three Reported Cases of Nosocomial Fungemia Caused by Candida auris

Abstract: Candida auris is a newly described species whose clinical significance is not clear. Here, we describe the first three cases of nosocomial fungemia caused by C. auris, which confirms that it is a causative agent of bloodstream infections. All three patients presented persistent fungemia for 10 to 31 days. The isolates obtained from the three patients were misidentified as Candida haemulonii and Rhodotorula glutinis by the Vitek 2 and the API 20C systems, respectively. C. auris was confirmed by sequence analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
356
0
28

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 410 publications
(425 citation statements)
references
References 9 publications
20
356
0
28
Order By: Relevance
“…Few researchers have in fact proved its pathogenic nature by performing histopathological study [11]. Instead, we studied the virulence traits of this isolate to reveal its pathogenic character.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few researchers have in fact proved its pathogenic nature by performing histopathological study [11]. Instead, we studied the virulence traits of this isolate to reveal its pathogenic character.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing isolation of C. auris from various clinical specimens clearly indicates its ability to colonise, invade and cause disease with varying severity. Though a limited number of studies have addressed this isolate, the majority of them have reported this species to be intrinsically resistant to azoles and amphotericin B [11]. C. auris is intrinsically less susceptible to fluconazole with propensity to develop high-level resistance.…”
Section: Discussionmentioning
confidence: 99%
“…C. haemulonii, C. haemulonii var. vulnera, C. duobushaemulonii, C. auris, and C. pseudohaemulonii are part of this group of rare clinical yeast that so far cannot be well differentiated by current commercial methods (17,23,30,34). Identification of these species should be based on molecular methods such as PCR, sequencing analyses, and MALDI-TOF MS analyses.…”
Section: Discussionmentioning
confidence: 99%
“…C. haemulonii and C. pseudohaemulonii were isolated from patients with central venous catheter-related fungemia, whereas the C. auris strains were isolated from the ear canals of inpatients (28). Moreover, the first three cases of bloodstream infection due to C. auris have been described recently (23).…”
mentioning
confidence: 99%
“…Although sequencing confirmed that the isolates were C. haemulonii group I, Candida pseudohaemulonii, or Candida auris, all were identified as C. haemulonii by the Vitek-2 YST yeast card system (bioMérieux, Marcy l'Étoile, France), and they were genetically closely related compared to other yeasts in the phylogenetic tree (12). Fungemia was the most common clinical presentation (8,10). Some blood isolates of C. haemulonii and C. pseudohaemulonii from fungemic patients exhibited high-level in vitro resistance to AMB and were associated with AMB therapeutic failure (8).…”
mentioning
confidence: 99%